Pengaruh Karakteristik Kewirausahaan Terhadap Kinerja UMK Agroindustri Pengolahan Kedelai di Kabupaten Lombok Tengah - Sharfina Nabilah; Tajidan Tajidan; Efendy Efendy; F.X. Edy Fernandez (Jurnal Social Economic of Agriculture, 2022)
Entrepreneurs are believed to be the driving wheel, and entrepreneurs are also considered as innovators in economic development. One form of entrepreneurship, namely UMK (Micro Small Business) can help the government as a driver of the economy by creating jobs. The purpose of this study was to analyze the effect of entrepreneurial characteristics on the performance of MSEs in soybean processing agroindustry in Central Lombok Regency. This research was conducted from April 2021 to October 2021 in Central Lombok Regency. The number of samples taken as many as 120 respondents. The data is processed both qualitatively and quantitatively. Qualitative data was processed descriptively while quantitative data was processed using Structural Equation Models (SEM) analysis. The results showed that (1) the entrepreneurial characteristics of soybean processing SMEs in Central Lombok Regency were divided into individual characteristics and psychological characteristics. The indicator of individual characteristics that has the greatest positive influence is business experience. Indicators of psychological characteristics that have the greatest positive influence are hard workers, (2) individual characteristics and psychological characteristics have a positive and significant effect on entrepreneurial competence. The biggest influence is shown by psychological characteristics, (3) individual characteristics have a positive and significant effect on business performance; while psychological characteristics have a negative and significant effect on business performance, (4) entrepreneurial competence has a negative and significant effect on business performance. That is, there is a decrease in benefits to the performance of the soybean processing agro-industry MSEs due to entrepreneurial competence.